Penerapan Metode Games dalam Meningkatkan Prestasi Belajar Penjasorkes Materi Gerak Dasar Lompat - Bagas Tiar Widigda; Andhega Wijaya; Rinda Kuswati (Departement of Mathematics Education, 2023)
In a class there are various characteristics of students, some are active and some are passive, so to foster motivation so that students or classes that are in a vacuum can receive lessons on a par with the others, you must use methods that can foster student motivation. The objective of this Classroom Action Research are: (1) To find out and describe the implementations of the Games Method in Physical Education learning in class IV SDN Bubutan IV Surabaya. (2) To find out the impact and analyze the implementation of the Games Method in increasing students' motivation and understanding of the subject matter in Physical Education learning in class IV SDN Bubutan IV Surabaya. Student learning outcomes seen from the pre-cycle table, cycle I, cycle II, and cycle III showed an increase. This is evidenced by the results of student learning in cycle I showing an average of 70.21, the percentage of scores above 70 achieved by students was only 30%. In cycle II, the average student score was 75.65, while the percentage of 70 and above was 91%. From these data, it shows that the game method in learning can increase the interest in learning Physical Education in the material of basic jumping motion.